Insight into the Prospects for Tumor Therapy Based on Photodynamic Immunotherapy - Xiaoxia Cheng; Yiqu Wei; Xiaomei Jiang; Chunli Wang; Mengyu Liu; Jiaxin Yan; Lei Zhang; Yaqi Zhou (MDPI AG, 2022)
Malignancy is one of the common diseases with high mortality worldwide and the most important obstacle to improving the overall life expectancy of the population in the 21st century. Currently, single or combined treatments, including surgery, chemotherapy, and radiotherapy, are still the mainstream regimens for tumor treatment, but they all present significant side effects on normal tissues and organs, such as organ hypofunction, energy metabolism disorders, and various concurrent diseases. Based on this, theranostic measures for the highly selective killing of tumor cells have always been a hot area in cancer-related fields, among which photodynamic therapy (PDT) is expected to be an ideal candidate for practical clinical application due to its precise targeting and excellent safety performance, so-called PDT refers to a therapeutic method mainly composed of photosensitizers (PSs), laser light, and reactive oxygen species (ROS). Photoimmunotherapy (PIT), a combination of PDT and immunotherapy, can induce systemic antitumor immune responses and inhibit continuing growth and distant metastasis of residual tumor cells, demonstrating a promising application prospect. This article reviews the types of immune responses that occur in the host after PDT treatment, including innate and adaptive immunity. To further help PIT-related drugs improve their pharmacokinetic properties and bioavailability, we highlight the potential improvement of photodynamic immunotherapy from three aspects: immunostimulatory agents, tumor-associated antigens (TAAs) as well as different immune cells. Finally, we focus on recent advances in various strategies and shed light on their corresponding mechanisms of immune activation and possible clinical applications such as cancer vaccines. Having discovered the inherent potential of PDT and the mechanisms that PDT triggers host immune responses, a variety of immunotherapeutic strategies have been investigated in parallel with approaches to improve PDT efficiency. However, it remains to be further elucidated under what conditions the immune effect induced by PDT can achieve tumor immunosuppression and to what extent PDT-induced antitumor immunity will lead to complete tumor rejection. Currently, PIT presents several outstanding intractable challenges, such as the aggregation ability of PSs locally in tumors, deep tissue penetration ability of laser light, immune escape, and biological toxicity, and it is hoped that these issues raised will help to point out the direction of preclinical research on PIT and accelerate its transition to clinical practice.